Abdominal Disturbances among Dengue Fever Patients - Arnold Hasahatan Harahap; Marcellus Simadibrata; Dadang Makmun; Irsan Hasan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Background: Abdominal disturbances are common symptoms found in approximately 40% of patients with dengue fever, which frequently cause significant morbidity. This study was developed as an attempt to understand the effect of plasma leakage in dengue hemorrhagic fever; particularly on ab dominal problems. Method: The study was conducted in hospitalized patients who were diagnosed with dengue fever and dengue hemorrhagic fever (based on the 1997 WHO criteria for DHF) at Fatmawati hospital, Jakarta, Indonesia. Abdominal ultrasonography (USG) was done on the fourth to sixth day in every patient and when necessary, endoscopy was done. Data were analyzed by Chi-square test. Results: Fifty-three (54.6%) patients had abdominal pain,  81 (83.5%) patients had nausea, 45 (46.4%) patients had excessive vomiting and 28 (28.9%) patients had diarrhea. Forty-seven (48.4%) patients had their aspartate aminotransferase (AST) elevated more than two fold of the Upper Normal Limit (UNL) level; 19 (20%) patients had their alanine aminotransferase (ALT) level elevated two fold higher than the UNL. Amylase was found to be two fold higher than the UNL only in 2 (2%) patients. Lipase level elevated two fold higher than the UNL in 11 (11.3%) patients. USG imaging showed that thickening of the gallbladder wall (over 3 mm) were observed in 83 (85.6%) patients. Endoscopic procedures showed erosive features particularly in the antrum, including edema of the gastric mucosa and widening of the gastric mucosa folding in four patients, while 4 (4.12%) patients had melena. Conclusion: Abdominal disturbances such as abdominal pain, vomiting, melena, liver enlargement and abnormal liver function as well as thickening of the gallbladder wall more than five mm are significantly high in patients with dengue hemorrhagic fever.   Keywords: abdominal disturbances, plasma leakage, dengue hemorrhagic fever